HOME OFFICE NA GESTÃO PÚBLICA - Cazella, Carla; Neusl , Elisandra (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
In the last year, the ways of working had to be changed, as the scenario changed and a health crisis was introduced. It was a worldwide pandemic caused by the virus scientifically called Sars-Cov-2, or as it is popularly known as Covid-19 (given the year of its appearance). In this context, the term home office became known, which translated into Portuguese is nothing more than a remote job. The spread of COVID-19 required several professionals to change their work routine and quickly adopt the home office regime, in addition to taking their work home full time, many people had to take over, without external help, the activities of care for their families and their homes; which considerably increased the quantity and diversity of demands. .The home office is no longer taboo in many companies that had to rush to adapt to remote work to face the covid-19 crisis. But after a year of home office, how are workers feeling?